x+3/x+5=X-1/x-4

Simple and best practice solution for x+3/x+5=X-1/x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3/x+5=X-1/x-4 equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

x+3/x+5 = X-(1/x)-4 // - X-(1/x)-4

x-X+3/x+1/x+4+5 = 0

1*x^1+4*x^-1+9*x^0 = 0

(1*x^2+9*x^1+4*x^0)/(x^1) = 0 // * x^2

x^1*(1*x^2+9*x^1+4*x^0) = 0

x^1

x^2+9*x+4 = 0

x^2+9*x+4 = 0

DELTA = 9^2-(1*4*4)

DELTA = 65

DELTA > 0

x = (65^(1/2)-9)/(1*2) or x = (-65^(1/2)-9)/(1*2)

x = (65^(1/2)-9)/2 or x = (-(65^(1/2)+9))/2

x in { (-(65^(1/2)+9))/2, (65^(1/2)-9)/2}

x in { (-(65^(1/2)+9))/2, (65^(1/2)-9)/2 }

See similar equations:

| 0.80y-8=0.40y+16 | | 20-4r=-4(-5r-5) | | 396p^2-539q^2=0 | | 0=-1/4*0 | | -3b+26=3(-6b+7)+5 | | 0=(-0)+4 | | h^2-9h+18= | | 2=4*2 | | 2=3*2 | | -12+6/3=-12+8/6 | | -34/2 | | 4+6/3=4+8/6 | | 4x+59=13 | | 2=1.1*2 | | (3x-1)(18)=414 | | (10+2z)+3z=3000 | | 0.33b+8=0.50b-4 | | -1/5-4 | | -.10(39)+.95x=.05(x-6) | | 4x^3+24x^2+170=0 | | 8x+15y=-38 | | y=7/10*1-7 | | 2(w-3)-6w=-30 | | 6xy-3x-18=0 | | y=7/10*0-7 | | 6-x=3x+6 | | 2=-5*2-8 | | (6x+1)+(-7x+7)= | | n^2+3n+4=0 | | 75t^10+35y^7= | | 2=4*2-3 | | 14x+21y=91 |

Equations solver categories